Hanging drop culture reprograms mesenchymal stem cell transcriptome to enhance cell delivery efficiency via attenuated pulmonary entrapment - Hsiang-Tzu Lee; Sheng-Yung Fu; Wei-Han Weng; Wei-Chen Chao; Yu-Pao Hsu; Nan-Ping Yang; Yu-Hsu Chen; Shau-Kwaun Chen; Chien-Wen Chang (Drug Delivery and Translational Research, 2025)
The three-dimensional (3D) culture system has emerged as an indispensable platform for modulating stem cell function in biomedicine, drug screening, and cell therapy. Despite a few studies confirming the functionality of 3D culture, the molecular factors underlying this process remain obscure. Here, we have utilized a hanging drop method to generate 3D spheroid-derived mesenchymal stem cells (3D MSCs) and compared them to conventionally 2D-cultured MSCs. The results showed that 3D MSCs exhibited distinct phenotypic features than 2D-cultured MSCs and expressed different transcriptional responses, as found from RNA-Seq analysis. Gene ontology (GO) annotations and KEGG pathway mapping pinpointed that the 3D MSCs responded more actively to incoming signals as they upregulated receptors and cytokine production while downregulating proteolysis-, cytoskeletal-, extracellular matrix-, and adhesion-related genes. Functionally, these MSCs also displayed enhanced chemotaxis and improved pulmonary transgression post-intravenous injection. This study provides mechanistic insights on addressing a significant limitation of MSC therapy: pulmonary entrapment after systemic delivery. Moreover, upregulated pluripotency-associated genes, such as Oct4, Sox2, and Nanog, suggest that the 3D MSCs possessed enhanced stemness and regenerative capacity. The results indicate that 3D spheroid culture reshapes MSC transcriptomic and functional profiles and emerges as a promising strategy for improving their therapeutic potential in regenerative medicine. Graphical abstract